2023
DOI: 10.1021/acsami.3c07947
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Heterojunction and Cu Vacancies in the Au@Cu2–xSe for the Enhancement of Electrochemical Nitrogen Reduction Performance

Yujin Jeong,
Gnanaprakasam Janani,
Dohun Kim
et al.

Abstract: The utilization of hydrogen (H 2 ) as a fuel source is hindered by the limited infrastructure and storage requirements. In contrast, ammonia (NH 3 ) offers a promising solution as a hydrogen carrier due to its high energy density, liquid storage capacity, low cost, and sustainable manufacturing. NH 3 has garnered significant attention as a key component in the development of next-generation refueling stations, aligning with the goal of a carbon-free economy. The electrochemical nitrogen reduction reaction (ENR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The Cu 2p spectra of Cu 0.10 -PC and Cu x Ce y -PC in Figure c exhibit four characteristic peaks as V 0 , V 1 , U 0 , and U 1 . Among the main peaks, V 0 and U 0 belong to Cu 2p 3/2 and Cu 2p 1/2 orbits of Cu 0/+ (in Cu 0.10 -PC) and Cu + (in Cu x Ce y -PC), respectively . The other peaks, V 1 and U 1 , are attributed to Cu 2p 3/2 and Cu 2p 1/2 orbitals of Cu 2+ species, , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The Cu 2p spectra of Cu 0.10 -PC and Cu x Ce y -PC in Figure c exhibit four characteristic peaks as V 0 , V 1 , U 0 , and U 1 . Among the main peaks, V 0 and U 0 belong to Cu 2p 3/2 and Cu 2p 1/2 orbits of Cu 0/+ (in Cu 0.10 -PC) and Cu + (in Cu x Ce y -PC), respectively . The other peaks, V 1 and U 1 , are attributed to Cu 2p 3/2 and Cu 2p 1/2 orbitals of Cu 2+ species, , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The TEM image and XRD pattern of para-Au/C after cyclic electrolysis displayed no obvious change, representing the structural robustness of para-Au/C (Figure S10). In addition, a 15 N isotope-labeling experiment was conducted to further quantify the product (Figure S11). The FE for NH 3 at −0.6 V vs RHE determined by 1 H NMR was approximated to the results detected via the UV−vis method (Figure S12).…”
Section: Catalytic Performance Of No 3 − Electroreductionmentioning
confidence: 99%
“…As one of the most fundamental industrial products, ammonia (NH 3 ) is not only an indispensable chemical in fertilizer, medicine, dye, and other industries but also an important carbon-free energy storage medium. Currently, the predominant method of NH 3 synthesis, the Haber–Bosch process, requires extreme reaction conditions of high temperature (400–500 °C) and high pressure (150–300 bar) with only 10–20% conversion efficiency. It is reported that the annual energy consumption for NH 3 synthesis accounts for 1–2% of the total global energy supply accompanied by about 1.5% of the global carbon emissions, leading to significant damage to the natural environment. Therefore, a clean and economical route for NH 3 production is urgently needed in pursuit of a sustainable chemical industry. …”
Section: Introductionmentioning
confidence: 99%
“…For example, it provides active sites for N 2 adsorption and activation to improve the eNRR performance of the catalyst; the electronic structure can be modified by defect engineering to change the reaction thermodynamics and kinetics. These defects include vacancies, structure effect, heterostructure, and so on. …”
Section: Introductionmentioning
confidence: 99%